Ethanol extract of Poria cocos induces apoptosis and differentiation in Neuro-2a neuroblastoma cells - Xia Jiang; Jie Xie; Zhaotun Hu; Xiaoliang Xiang (Bangladesh Pharmacological Society, 2022)
Poria cocos is a widely used ingredient in traditional Chinese medicine and dietary supplement. In this study, the effects of the ethanol extract of P. cocos on cell proliferation in Neuro-2a neuroblastoma cells and its possible mechanism of action are investigated. The extract inhibited the growth of Neuro-2a cells in a dose-dependent manner with an IC50 value of 34.6 μg/mL. To further elucidate the mechanism by which the extract acts, transcriptome analysis using high-throughput Illumina RNA-seq technology was performed. Transcriptome analysis revealed that the cell cycle as the potential primary target pathway of the extract in Neuro-2a cells. Flow cytometry analysis confirmed that the extract induced cell cycle arrest at G1 phase. Furthermore, the extract also induced apoptosis in Neuro-2a cells. Notably, it was found that Neuro-2a cells exhibited morphological features of differentiation when treated with the extract. This study suggests that P. cocos may be a potential candidate therapeutic agent in combating neuroblastoma.